Penguatan Merek Madrasah Melalui Pengelolaan Program Kurikulum di Madrasah Ibtidaiyah Darul Hikmah Bantarsoka - Harisatunisa, Harisatunisa; Laras, Srikandi Tri Wahyu (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
One of the main challenges to the sustainability of private educational institutions has been their ability to attract student interest, as private schools are often perceived as a second-choice option. The ability of madrasahs to manage their brand effectively remains a significant challenge to the sustainability of private madrasahs. Madrasah Ibtidaiyah Darul Hikmah Bantarsoka is one such private madrasah in Purwokerto that has succeeded in maintaining its institutional brand through effective curriculum management. This study aims to provide an overview of the brand strengthening process of the madrasah through the curriculum management program at Madrasah Ibtidaiyah Darul Hikmah Bantarsoka. Employing a qualitative approach with a case study design, data were collected through interviews and document analysis. The findings of this study reveal that brand strengthening at Madrasah Ibtidaiyah Darul Hikmah Bantarsoka is carried out through the reinforcement of brand identity by implementing an Islamic education curriculum based on the values of Ahlusunnah Wal Jamaah. Furthermore, the madrasah fosters a positive brand experience by collaborating with parents in the implementation of curriculum programs. The madrasah also builds a positive brand image through digital marketing of its curriculum programs. The final effort in maintaining brand performance involves the effective allocation of teaching staff resources in the implementation of curriculum programs. A limitation of this study is that the perspective is solely from the madrasah as the service provider, without involving the parents of the students.